1994
DOI: 10.1021/bi00198a003
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a Myristoyl-ACP-Specific Thioesterase from Vibrio harveyi

Abstract: The crystal structure of a myristoyl acyl carrier protein specific thioesterase (C14ACP-TE) from a bioluminescent bacterium, Vibrio harveyi, was solved by multiple isomorphous replacement methods and refined to an R factor of 22% at 2.1-A resolution. This is the first elucidation of a three-dimensional structure of a thioesterase. The overall tertiary architecture of the enzyme resembles closely the consensus fold of the rapidly expanding superfamily of alpha/beta hydrolases, although there is no detectable ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(82 citation statements)
references
References 48 publications
2
80
0
Order By: Relevance
“…The two thioesterases share the core six-stranded ␤-sheet, although ACTE also contains the antiparallel strands ␤1 and ␤2 at the N-terminal end, as well as a longer C terminus, which contains an additional ␣-helix and ␤-strand. The insertion between ␤6 and ␤7 that forms the palmitate binding domain corresponds topologically to the smaller ''cap'' subdomain predicted form the myristoylbinding pocket in ACTE (12), but it is structurally quite different. PPT1 and ACTE have a common catalytic triad and acyl transfer mechanism, but differ in specificity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The two thioesterases share the core six-stranded ␤-sheet, although ACTE also contains the antiparallel strands ␤1 and ␤2 at the N-terminal end, as well as a longer C terminus, which contains an additional ␣-helix and ␤-strand. The insertion between ␤6 and ␤7 that forms the palmitate binding domain corresponds topologically to the smaller ''cap'' subdomain predicted form the myristoylbinding pocket in ACTE (12), but it is structurally quite different. PPT1 and ACTE have a common catalytic triad and acyl transfer mechanism, but differ in specificity.…”
Section: Resultsmentioning
confidence: 99%
“…The Vibrio harveyi myristoyl-acyl carrier protein thioesterase (ACTE) (12), an enzyme involved in bioluminescence, contains the ␣͞␤ hydrolase fold characteristic of microbial lipases. The second, 4-hydroxybenzoyl-CoA thioesterase from Pseudomonas sp.…”
Section: Nfantile Neuronal Ceroid Lipofuscinosis (Incl) Is the Mostmentioning
confidence: 99%
“…Extensive searches in current sequence data bases failed to uncover any significant relationships of FatAlB with any other entry. Even the known non-plant acyl-ACP thioesterases (Lawson et al, 1994) appear to have a different origin. To date, therefore, no clues for the evolutionary source of Fat, which could have assisted with the evaluation of its original specificity, have been uncovered by this approach.…”
Section: Evolution Of Plant Acylacp Thioesterasesmentioning
confidence: 99%
“…Structural studies and the use of specific inhibitors such as diisopropylfluorophosphate have indicated that a serine residue forms the catalytic centre in many functionally diverse hydrolytic enzymes such as proteases [ 11, triacylglycerol lipases [2-51, acetylcholinesterases [6-71, butyrylcholinesterases [8], thioesterases [9], cholesterol esterases [lo] and even a peroxidase [11]. In most esterases, the serine forms part of a catalytic triad comprising histidine, serine and a carboxylic acid, and it has been postulated that the triad functions to increase the nucleophilicity of catalytic serine residue by means of a chargerelay system [l].…”
mentioning
confidence: 99%